Fulfilling professional tasks by nurses in care of a patient after retina transplantation - Piotrkowska, Renata; Książek, Janina; Konarska, Gabriela; Terech, Sylwia (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Retina transplantation called keratoplasty has the best prognosis of all procedures in transplantology. In recent years about 100 thousands transplantations per year are carried out, 500 of which take place in Poland. Nurses who care of the patients after retina transplantation perform responsible tasks which require a high professional qualification. Aim of the study. The aim of the research is to evaluate the aspect of carrying out professional tasks by nurses in the care of a patient after retina transplantation. Material and methods. The material comprised a patient after retinal transplantation hospitalized in a clinic of a hospital in Gdańsk. Individual case study was used in the research, as techniques the authors used an interview, observation and records analysis: case history and nursing care history. Results and conclusions. The problems of biological nature dominated in the nursing care process of the patient. Nurses fulfilled mostly caring and the therapeutic functions, a limited significance was attached to rehabilitation and health promotion. Keeping a balance between dealing with identified nursing problems and an ability to fulfill all the professional functions makes a significant challenge for nurses. Nursing Topics 2010; 18 (3): 323-328